Exploring managers' and supervisors' experiences of supporting breastfeeding at work: A qualitative study among clothing factory workers in South Africa - Junglee, Bibi Sharfa (Organisational Psychology, 2022)
This study focuses on understanding supervisors' and managers' experiences of supporting breastfeeding support at work in the context of clothing factories in the Western Cape, South Africa. Return to full-time employment after maternity leave is the leading cause affecting mothers' breastfeeding decisions. A qualitative, exploratory research design was used. Secondary qualitative data from 17 in-depth semi-structured interviews with supervisors and managers were analysed using a thematic analysis approach. Three major themes emerged: Influence of supervisors' socio- cultural beliefs and personal experiences on support orientation; Navigating productivity, mothers' breastfeeding needs, and co-worker emotions; and the nature of maternity and breastfeeding conversations. Drawing from the study findings, implications for managerial practices and policy recommendations are proposed to advance managerial and supervisory support for breastfeeding at work in low-income workplaces.